Impact of Climate Change on Water Availability in Water Source Areas of the South-to-North Water Diversion Project in China - Qiao, Cuiping; Ning, Zhongrui; Wang, Yan; Sun, Jinqiu; Lin, Qianguo; Wang, Guoqing (Frontiers in Earth Science, 2021)
The South-to-North Water Diversion Project (SNWD project) is a mega water project designed to help solve water shortages in North China. The project’s management and operation are highly influenced by runoff change induced by climate change in the water source areas. It is important to understand water availability from the source areas in the context of global warming to optimize the project’s regulation. Based on the projections of nine GCMs, the future runoff in the water source areas of the three diversion routes were simulated by using a grid-based RCCC-WBM (Water Balance Model developed by Research Center for Climate Change) model. Results show that temperature will rise by about 1.5 degrees in the near future (2035, defined as 2026-2045) and 2.0 degrees in far future (2050, defined as 2041-2060) relative to the baseline period of 1956-2000. Although GCM projections of precipitation are highly uncertain, the projected precipitation will likely increase for all three water source areas. As a result of climate change, the simulated runoff in the water source areas of the SNWD project will likely increase slightly by less than 3% relative to baseline period for the near and far future. However, due to the large dispersion and uncertainty of GCM projections, a high degree of attention should be paid to the climate-induced risk of water supply under extreme situations, particularly for the middle route of the SNWD project.